Extraction of A Four Rooted Maxillary Third Molars: A Case Series of Rare Occurrence.: Life Sciences -Dentistry - Mukram Ali, Fareedi; Somili, Alanood Mansour; Shabi, Afnan Yahya; Ustad, Farheena; Gadah, Thuraya Saleh; Suleman, Ghazala; Mohammed Mahzari, Rashed Hussain; Ali Areshi, Raneem Abdullah (International Journal of Life Science and Pharma Research, 2023)
It is uncommon to find maxillary molars with four roots, known to have three roots (two buccal and one palatal); it might also havethree, sometimes fused roots. Maxillary third molars have a wide range of morphologies, making it challenging clinically and difficult to distinguishthem radiographically. Given the proximity of the maxillary tuberosity and the floor of the maxillary antrum, the presence of an accessory rootmay complicate a rather straightforward exodontia of the maxillary third molar. We present a case series of three maxillary third molarextractions. The extracted tooth had four roots, an unusual variation in root shape. This case series focuses on morphological changes in theroots of maxillary third molars that are difficult to detect on routine radiographs. Also, this case series highlights the potential for extensivemorphological variation in the maxillary third molar, which could make a simple extraction challenging. To avoid difficulties, cautious extractionmaneuvering is required. Hence it is advisable to prepare for the possibility of an accessory root on a maxillary molar in endodontic and oralsurgical clinical practice to prevent difficulties after surgery. The lesson to be learned from this case series is there can be a possibility for an extraroot in the maxillary third molar, and the dentist must always be alert.Keywords: , , , ,